Integrating Multi-Hazard Risk Analysis into Spatial Planning for Small Island: Study Case of Sangihe Island. Issue 1 (June 2021) - Hadianti, Atrida; Ulinnuha, Hilmiyati; Heliani, Leni Sophia; Sarwadi, Ahmad; Kurniawan, Adhy; Budisetiawan, Juswono; Suhubawa, Latif; Suryanto, Wiwit; Pratama, Cecep; Mutaqin, Bachtiar Wahyu; Nayati, Widya; Bayumurti, Yosi; et al.
Abstract: Small island regions are facing disaster risks due to their exposure to various hazards, e.g. floods, landslide, and earthquake. In order to achieve long-term disaster resilience, one of the significant strategies is applying spatial planning based on disaster risk reduction. Methods for multi-hazard risk assessment and risk analysis have been broadly discussed, nevertheless, its implementation in spatial planning is inadequate. In this study, we conducted a multi-hazard risk mapping of Sangihe Island and reviewed its spatial plan. It is identified that disaster risk analysis hardly meets its standard in consequence of insufficient secondary data availability. Also, the spatial plan merely utilizes hazard maps for consideration, not yet as risk analysis, resulting in allocating vital elements in high-risk areas. Hence, secondary data support is necessary for accordance with the needs of standardized risk analysis and is updated regularly. Furthermore, integration of risk analysis into spatial planning is required to determine the direction of development, which not only reduces exposure to hazards but emphasizes more towards the capacity building to reduce vulnerability.